The Maternal Serum Alpha-Fetoprotein for Congenital Anomalies Screening - Patria Dewi Pande; Jusak Nugraha (WMJ (Warmadewa Medical Journal), 2023)
Screening examination for maternal, especially serum, is a non-invasive examination of the fetus’s condition. During pregnancy, screening examinations are performed in women recommended for ultrasonography (USG), amniocentesis, or other obstetric interventions. There are three markers for maternal serum screening: alpha-fetoprotein, human chorionic gonadotropin (hCG), and unconjugated estriol. Maternal serum alpha-fetoprotein is useful for screening aneuploidies and neural tube defects. This examination, besides seeing congenital abnormalities, can be used for the risk of pregnancy complications such as placental insufficiency, intrauterine growth restriction, preeclampsia, and intrauterine fetal death. Laboratory methods for examining maternal serum alpha-fetoprotein are radioimmunoassay and microparticle capture enzyme immunoassay. Keywords: Screening, Pregnancy, Alpha-Fetoprotein, Laboratory